MULTIDIMENSIONAL PAIN AND SYMPTOM ASSESSMENT SCALE FOR ELDERLY PEOPLE IN PALLIATIVE CARE - Jossiana Wilke Faller; Adriana Zilly; Cynthia Borges de Moura; Pedro Henrique Brusnicki (Universidade Federal do Paraná, 2016)
The objective was to assess pain and associated symptoms in elderly cancer patients in home-based palliative care. Quantitative and cross-sectional study involving 33 elderly in Foz do Iguaçu, state of Paraná, Brazil, between January and May 2015, using the Edmonton Symptom Assessment System and analyzed using descriptive statistics. The prevalent age range of the elderly was between 60 and 69 years old, mostly women, married, suffering from breast cancer, low income and low education, with other diseases associated with cancer. It was verified that 90.1% of the patients mention daily and continuous moderate burning pain in the site affected by the tumor. The associated symptoms were anxiety, fatigue, depression and reduced wellbeing. Pain and symptom control measures need to be readjusted and health managers need to invest further in order to permit better palliative care at home.